Politik Luar Negeri Indonesia terhadap Asean dalam Menciptakan Ketahanan Regional (1967-1993): Indonesia's Foreign Policy Towards ASEAN in Maintaining Regional Resilience (1967-1993) - Perpustakaan UGM, i-lib ([Yogyakarta] : Lembaga Penelitian dan Pangabdian kepada Masyarakat, Universitas Gadjah Mada, 2003)
This research studies the Indonesia's foreign policy to ASEAN for maintaining regional resilience in Southeast Asia during the 1967-1993 period. It specifically intends to explore the idea of Indonesia on regional resilience in Southeast Asia and the consequence of this idea on the ASEAN formal attitude holds on the regional resilience in Southeast Asia region. This library research in which the data are derived from documentary resources : books, journals, news papers, magazines, related to the topic of the research. The data are generalized and then analized qualitatively to draw the conclusion. The conclusion from the research results is that idea of Indonesia on the regional resilience in Souheast Asia region is to build Souheast Asia which is anticonfrontation, solid cooperative and free from external intervention in dealing with regional security while prioritizing regional neutrality using ASEAN as a means of actualizing this ideas and giving strong commitment to ASEAN. The consequence from this ideas is the ASEAN formal attitude holds in coping with the issue on secutity stability in Souheast Asia such as: (1) promoting the spirit of solidarity and collectivity among the ASEAN members, (2) adopting free and neutral position to forign power in building regional security stability, (3) exercising peaceful manners in settling a conflict by not using a means of violence nor weapon, but strengthening cooperation, dialogue, talks for concensus, and refusing external intervention as well as prioritizing regionally oriented conflict settlement in ASEAN, (4) expanding the ASEAN membership and mutual cooperation in politics and security.